FENOMENA POLITISASI BIROKRASI SELAMA PILKADA DI INDONESIA - Wisnu Yuda Pratama; Muh. Afif Baihaq; Asy'Ari Wais Alqorni (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
The politicization of the bureaucracy which is a pathology in the body of the bureaucracy in Indonesia still thrives when general elections are held. ASN mobilization during regional elections, post-election post-election compensation, and removal of career positions for political reasons often have implications for the performance of bureaucratic substance which will decline due to complex reasons. The writing method uses a qualitative study approach with the desk research method. This study seeks to dig up data from various sources as secondary data in order to describe phenomena of bureaucratic politicization, rules governing ASN actions and the use of the merit system as a bureaucratic measure to maintain the neutrality principle of ASN in regional elections over the substance of the rules in force. The neutrality of ASN which has changed due to political intervention has led to a